Multiple factors affect the evolution of repertoire size across birds. (29th March 2021) - Leighton, Gavin M; Birmingham, Tucker
Abstract: Changes in signaling repertoires across species allow for insight into the macroevolutionary forces that control signaling systems. Signaling systems are theorized to be affected by both the social and ecological environments of species. With respect to social variables, increased social complexity is thought to lead to increased vocal complexity. Although ecology can affect signaling systems in numerous ways, one potential effect of ecology is that more cluttered habitats should lead to greater reliance on nonvisual (e.g., vocal) signals. To test these concepts on a macroevolutionary scale, we compiled a large dataset of avian vocal repertoires. We amassed vocal repertoires for 821 species of birds and for many of these species categorized their vocalizations into usage categories (e.g., alarm, contact). To analyze the social and ecological forces that act on repertoire evolution, we incorporated datasets with several social variables (e.g., cooperative breeding and length of social bond), and included data on the habitat and foraging behaviors of species within the dataset. We used Bayesian phylogenetic analysis to test for potential relationships within the data. We found that cooperative breeding was a significant predictor of larger repertoire size in birds; we also find several, more targeted effects. For instance, foraging strata affected repertoire size and repertoire composition. In sum, we find considerable evidence that social features affect repertoire size while certain ecological variables have more targeted effects on vocal repertoires. Abstract : The evolution of complex communication systems has long intrigued biologists as explanations of these communication systems in other species might shed light on how the intricate language of humans has evolved. The evolution of larger communication systems in birds is largely driven by species with complex social systems. The evolution of sociality might therefore explain the evolution of complex communication systems.